Changes in Mortality Related to Traumatic Brain Injuries in the Seychelles from 1989 to 2018 - Abio Anne; Bovet Pascal; Valentin Bernard; Barnighausen Till; Shaikh Masood Ali; Posti Jussi P; Wilson Michael Lowery (FRONTIERS MEDIA SA, 2022)
Introduction: Traumatic Brain Injuries (TBIs) are a significant source of disability and mortality, which disproportionately affect low- and middle-income countries. The Republic of Seychelles is a country in the African region that has experienced rapid socio-economic development and one in which all deaths and the age distribution of the population have been enumerated for the past few decades. The aim of this study was to investigate TBI-related mortality changes in the Republic of Seychelles during 1989–2018.
Methods: All TBI-related deaths were ascertained using the national Civil Registration and Vital Statistics System. Age- and sex-standardised mortality rates (per 100,000 person-years) were standardised to the age distribution of the World Health Organisation standard population.
Results: The 30-year age-standardised TBI-related mortality rates were 22.6 (95% CI 19.9, 25.2) in males and 4.0 (95% CI 2.9, 5.1) in females. Road traffic collisions were the leading contributor to TBI-related mortality [10.0 (95% CI 8.2, 11.8) in males and 2.7 (95% CI 1.8, 3.6) in females, P > 0.05]. TBI-related mortality was most frequent at age 20–39 years in males (8.0) and at age 0–19 in females (1.4). Comparing 2004–2018 vs. 1989–2003, the age-standardised mortality rates changed in males/females by −20%/−11% (all cause mortality), −24%/+39.4% (TBIs) and +1%/+34.8% (road traffic injury-related TBI).
Conclusion: TBI-related mortality rates were much higher in males but decreased over time. Road traffic collisions were the single greatest contributor to TBI mortality, emphasising the importance of road safety measures.